Inﬂuence on wine biogenic amine composition of modiﬁcations to soil N availability and grapevine N by cover crops - Pérez-Alvarez, Eva (2018)
BACKGROUND: Vineyard soil management can modify the nitrogen soil availability and, therefore, grape amino acid content. These compounds are precursors of biogenic amines, which have negative eﬀects on wine quality and human health. The objectivewastostudywhethertheeﬀectofconventionaltillageandtwocovercrops(barleyandclover)ongrapevinenitrogen status could be related to wine biogenic amines. Over 4 years, soil NO3−-N, nitrogen content in leaf and wine biogenic amine concentrationweredetermined. RESULTS: Barley reduced soil NO3−-N availability and clover increased it. In 2011, at bloom, nitrogen content decreased with barley treatment in both blade and petiole. In2012,nitrogen content in both leaf tissues at bloom was greater with clover than with tillage and barley treatments.Also,total biogenic amines decreased in barley with respect to tillage and clover treatments. There were correlations between some individual and total biogenic amine concentrations with respect to nitrogen content in leaf tissues. CONCLUSION:Wine biogenic amine concentration can be aﬀected by the grapevine nitrogen status, provoked by changes in the soil NO3−-N availability with both cover crop treatments